REBT-Based Individual Counseling to Overcome Verbal Bullying Behavior - Nakhma'ussolikhah; Hara Permana; Sulistianingsih Sulistianingsih; Diah Purnama; Lina Marliani; Muslimah Muslimah; Ficky Adi Kurniawan (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
Mistakes in understanding perception result in gaps in thought patterns and behavior. The aim of this research is to determine the condition of behavior of victims of verbal bullying , to find out the stages of efforts of REBT-based individual counseling services in dealing with students due to verbal violence. This research is a type of qualitative research with a case study approach. Qualitative research is based on primary and secondary data. Primary data was obtained through participatory observation , in-depth interviews with three students who were victims of bullying and one guidance and counseling teacher, documentation in the form of counseling protocols and counseling record cards. This research shows that counseling (REBT) is effective in dealing with students who are victims of verbal bullying. Guidance teachers explore component A (events), component B (beliefs and thoughts), and components C/D/E (feelings, behavior and results). After students internalize REBT, there is a change in attitude and positive perception of the negative impacts they experience. This research found several changes in thought patterns, increased morality, solidarity and increased awareness of the strength of personal mentality due to verbal violence. Aspects of students' mental development become better after individual counseling.